My Sailor, My Love (DVD) - Cosmo, James; Brennan, Brid; Walker, Catherine ([United States] : Music Box Films, 2024)
Howard is a widowed sailor living alone on the coast of Ireland. His daughter, Grace, hires Annie, a lovely older woman to help around the house. Initially resistant to this support, Howard is soon charmed by Annie's gentle care, and the two fall in love. This new romance illuminates the hurt within Howard's relationship with Grace, tearing at Howard and Annie's seaside love story.
01/30/2024
new dvd 2024 winter.
Director, Klaus Haro.
James Cosmo, Brid Brennan, Catherine Walker.
DVD.
English audio.
Keywords: Drama; Drama